2021
DOI: 10.3390/horticulturae8010008
|View full text |Cite
|
Sign up to set email alerts
|

High NH4+/NO3− Ratio Inhibits the Growth and Nitrogen Uptake of Chinese Kale at the Late Growth Stage by Ammonia Toxicity

Abstract: The aim of this study was to determine the effects of various NH4+/NO3− ratios in a nutrient solution on the growth and nitrogen uptake of Chinese kale under hydroponic conditions. The four NH4+/NO3− ratios in the nutrient solution were CK (0/100), T1 (10/90), T2 (25/75), and T3 (50/50). An appropriate NH4+/NO3− ratio (10/90, 25/75) promoted the growth of Chinese kale. T2 produced the highest fresh and dry weight among treatments, and all indices of seedling root growth were the highest under T2. A high NH4+/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The appropriate NH 4 + :NO 3 - ratio promotes plant growth, and different species require different optimal NH 4 + :NO 3 - ratios. For example, the optimal NH 4 + :NO 3 - ratio is 0:100 for yellow flag ( Chang et al., 2010 ) and wheat ( Yang et al., 2021 ); 25:75 for Chinese cabbage cultivars ( Chen et al., 2005 ; Zhu et al., 2021 ), strawberry ( Tabatabaei et al., 2006 ), tomato ( Liu et al., 2017 ), Chinese kale ( Wang et al., 2021 ), and lettuce ( Du et al., 2022 ); 50:50 for cabbage ( Zhang et al., 2007 ), Sweet flag ( Chang et al., 2010 ), coffee ( Carr et al., 2020 ), soybean ( Raza et al., 2021 ), and blackberry ( Wei et al., 2023 ); 75:25 for pecan ( Chen et al., 2021 ); and 83:17 for blueberry ( Zhang et al., 2021 ). In this study, the effects of different NH 4 + :NO 3 - ratios on the growth parameters of centipedegrass were monitored and the NH 4 + :NO 3 - ratio of 50:50 treatment had the highest biomass and carbon and nitrogen accumulation ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate NH 4 + :NO 3 - ratio promotes plant growth, and different species require different optimal NH 4 + :NO 3 - ratios. For example, the optimal NH 4 + :NO 3 - ratio is 0:100 for yellow flag ( Chang et al., 2010 ) and wheat ( Yang et al., 2021 ); 25:75 for Chinese cabbage cultivars ( Chen et al., 2005 ; Zhu et al., 2021 ), strawberry ( Tabatabaei et al., 2006 ), tomato ( Liu et al., 2017 ), Chinese kale ( Wang et al., 2021 ), and lettuce ( Du et al., 2022 ); 50:50 for cabbage ( Zhang et al., 2007 ), Sweet flag ( Chang et al., 2010 ), coffee ( Carr et al., 2020 ), soybean ( Raza et al., 2021 ), and blackberry ( Wei et al., 2023 ); 75:25 for pecan ( Chen et al., 2021 ); and 83:17 for blueberry ( Zhang et al., 2021 ). In this study, the effects of different NH 4 + :NO 3 - ratios on the growth parameters of centipedegrass were monitored and the NH 4 + :NO 3 - ratio of 50:50 treatment had the highest biomass and carbon and nitrogen accumulation ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, those studies mainly concentrate on Chinese cabbage ( Chen et al., 2005 ; Hu et al., 2017 ), strawberry ( Tabatabaei et al., 2006 ), cabbage ( Zhang et al., 2007 ), tomato ( Liu et al., 2017 ), maize ( Wang et al., 2019b ), coffee ( Carr et al., 2020 ), purple coneflower ( Ahmadi et al., 2021a ; Ahmadi et al., 2021b ; Ahmadi et al., 2022 ), pecan ( Chen et al., 2021 ), soybean ( Raza et al., 2021 ), Chinese kale ( Wang et al., 2021 ), wheat ( Yang et al., 2021 ), blueberry ( Zhang et al., 2021 ), flowering Chinese cabbage ( Zhu et al., 2021 ), lettuce ( Du et al., 2022 ), and blackberry ( Wei et al., 2023 ), with little attention given to grass plants. The growth promotion triggered by an appropriate NH 4 + :NO 3 - ratio is attributed to the accumulation of more carbon and nitrogen ( Chen et al., 2005 ), a higher leaf area and photosynthetic rate ( Tabatabaei et al., 2006 ; Hu et al., 2017 ; Liu et al., 2017 ; Wang et al., 2019b ; Carr et al., 2020 ; Raza et al., 2021 ; Zhang et al., 2021 ), a higher chlorophyll concentration ( Liu et al., 2017 ; Raza et al., 2021 ), increased auxin synthesis ( Wang et al., 2019b ), improved absorption of H 2 PO 4 – , K + , Ca 2+ , and Mg 2+ nutrients and a suitable proportion of nitrogen assimilation and storage ( Zhang et al., 2007 ; Carr et al., 2020 ), improved root growth and root/shoot ratio ( Ahmadi et al., 2021b ; Raza et al., 2021 ; Zhang et al., 2021 ), or maintenance of the pH value and NH 4 + :NO 3 - ratios of the nutrient solution ( Wang et al., 2021 ; Zhu et al., 2021 ). However, information regarding the role of plant micromorphological structure in growth promotion and the early-stage response of the above physiological parameters to the changes of different NH 4 + :NO 3 - ratios is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Where data exists regarding CEA systems, it is usually highly bespoke to the system design and conditions of the experiment, thus direct comparisons are difficult to make. Studies carried out on salad crops in CEA systems have shown a wide range of N‐NUEs, covering two orders of magnitude (2%–104%) (e.g., Consentino et al, 2022; Djidonou & Leskovar, 2019; Pennisi et al, 2019; Santamaria et al, 2002; Yang & Kim, 2020; Wang et al, 2021) (Table 4). Data are more difficult to find for other elements to make comparisons, which are poorly represented in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other than that, there is a need to conduct a field test study to refine the existing data obtained by previous researchers such as Di Mola et al (2020), Xiang et al (2019), and Y. Wang et al (2022), who also studied about the nitrogen uptake by leafy vegetables like Chinese kale plant. Therefore, this study attempted to investigate the effect of RHA addition to palm oil-based compost in enhancing the nitrogen uptake by the Chinese kale plant.…”
Section: Introductionmentioning
confidence: 99%